A combination of Vitamin D3 and Epigallocatechin Gallate significantly inhibits leiomyoma growth in an experimental animal model - A. Goker; S. Micili; B. Ergur; N. Kuscu (International Journal of Medical Device and Adjuvant Treatments, 2022)
OBJECTIVE: Leiomyoma, or uterine fibroid, is the most common benign gynecological neoplasm. It can cause abnormal uterine bleeding, pain, urinary incontinence, constipation and dyspareunia. Hysterectomy is the most used treatment. Currently great efforts are carried out to find alternative therapeutic strategies. Among them, vitamin D and epigallocatechin gallate administration gave promising results. We developed a rat leiomyoma model to investigate their mechanisms of action and evaluate their effects.